Prevalence of anemia during pregnancy and its association with adverse perinatal outcomes in Madhya Pradesh, India - Sinha, Divya; Shrivastava, Swati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The prevalence of anemia in India is increasing day by day and covers almost one third population. Anemia during pregnancy leads many perinatal complications such as miscarriage, abortion and still birth. So, the aim of the study was to determine prevalence of anemia during pregnancy and its association with adverse perinatal outcomes in region of Madhya Pradesh. Methods: The study population consisted of 15-49 years women of reproductive age group from the state Madhya Pradesh, India, which were taken from the National Family Healthy Survey-4 (2015-16). Various perinatal outcomes along with age and residence was cross tabulated and frequencies were generated. The chi-square statistic was used to test the significance. Results: In severe anaemic women prevalence of miscarriage (74.0%) was statistically significantly higher (p<0.05) as comparison to other forms of anemia. Also, in the age group 25-29 years and rural population prevalence of miscarriage (40% and 55%) was highly significant (p<0.001) as comparison to other age group and urban population. Conclusions: The severity of anemia is directly proportional to poor and adverse perinatal outcomes in pregnancy.